2008
DOI: 10.1126/science.1149180
|View full text |Cite
|
Sign up to set email alerts
|

A Mosaic of Chemical Coevolution in a Large Blue Butterfly

Abstract: Mechanisms of recognition are essential to the evolution of mutualistic and parasitic interactions between species. One such example is the larval mimicry that Maculinea butterfly caterpillars use to parasitize Myrmica ant colonies. We found that the greater the match between the surface chemistry of Maculinea alcon and two of its host Myrmica species, the more easily ant colonies were exploited. The geographic patterns of surface chemistry indicate an ongoing coevolutionary arms race between the butterflies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
205
6
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(226 citation statements)
references
References 20 publications
8
205
6
1
Order By: Relevance
“…Examples like these of coevolutionary mosaics continue to be found each year, now that researchers are asking how these mini-coevolutionary "experiments" have been shaped by selection in different ways in different places Thrall et al 2002;Laine 2005;Thompson and Fernandez 2006;Nash et al 2008;Toju 2008;Anderson and Johnson 2009;King et al 2009;Johnson and Anderson 2010;Medel 2010). Meanwhile, multiple researchers are generating their own geographic mosaics by constructing complex microcosms in the laboratory (e.g., connected flasks).…”
Section: Interactions Coevolve As Constantly Changing Geographic Mosaicsmentioning
confidence: 99%
“…Examples like these of coevolutionary mosaics continue to be found each year, now that researchers are asking how these mini-coevolutionary "experiments" have been shaped by selection in different ways in different places Thrall et al 2002;Laine 2005;Thompson and Fernandez 2006;Nash et al 2008;Toju 2008;Anderson and Johnson 2009;King et al 2009;Johnson and Anderson 2010;Medel 2010). Meanwhile, multiple researchers are generating their own geographic mosaics by constructing complex microcosms in the laboratory (e.g., connected flasks).…”
Section: Interactions Coevolve As Constantly Changing Geographic Mosaicsmentioning
confidence: 99%
“…After spending 10-15 days feeding on a species-specific food plant, Maculinea larvae drop to the ground and wait until they are found and carried into an ant nest by a Myrmica worker (Elmes et al 1991a;Akino et al 1999;Elmes et al 2002;Thomas 2002). Adoption of the parasite caterpillars by the host ants is mediated by chemical deception (Akino et al 1999;Schönrogge et al 2004;Nash et al 2008;FĂŒrst et al 2011). Once in the ant colony, butterfly larvae make use of different feeding strategies: Maculinea alcon and M. rebeli are called "cuckoo feeders" because their larvae are fed directly by the ant workers by trophallaxis (Elmes et al 1991b;Thomas & Elmes 1998), while M. arion and M. teleius are "predatory species" and directly prey on ant brood.…”
Section: The Case Of Maculinea Butterfliesmentioning
confidence: 99%
“…So far, in Large Blue butterflies, there are 11 microsatellite markers for P. nausithous and one for P. alcon (Zeisset et al, 2005), which have been successfully used in population studies (Anton et al, 2007;Nash et al, 2008). A cross-species experiment indicated that nine of these markers can be amplified in P. teleius with eight of them showing polymorphism, and four were amplified and appeared to be polymorphic in P. alcon (see Table 2 in Zeisset et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Anton et al (2007) used them to evaluate the level and pattern of gene flow among fragmented populations of P. nausithous and its specific parasitoid, and Nash et al (2008) to characterize genetic differentiation among populations of P. alcon and its potential host ant species.…”
Section: Introductionmentioning
confidence: 99%